Greenhouses in the tropics - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
An international symposium on design and environmental control of tropical and subtropical greenhouses will take place from April 15 to 18, 2001, in Taichung, Taiwan. Reduced registration fees apply to members of the International Society for...